Automation-aided construction and characterization of Bacillus subtilis PrsA strains for the secretion of amylases - Hamburger, Felix; Schlichting, Niels; Eichenlaub, Michael; Costea, Paul Igor; Sauer, Christopher; Jenewein, Stefan; Kabisch, Johannes (Frontiers in Bioengineering and Biotechnology, 2025)
Proteins face an obstacle race on their way to successful folding. Chaperones facilitate the proper folding of proteins by ensuring they remain on the correct path toward their final tertiary structure. In bacilli, the PrsA chaperone is essential for the correct folding and stabilization of proteins within the cell wall. Overexpression of the PrsA chaperone has been shown to improve the successful folding and secretion of many biotechnologically relevant secreted enzymes. This resulted in a double benefit: firstly, it promotes the efficient release of properly folded enzymes from the cell wall, and second, it reduces the folding stress for the cell, thereby enhancing the overall fitness of the production organism. This paper presents a workflow in which different wild-type PrsA molecules in Bacillus subtilis are co-expressed with different amylases having different signal peptides and promoters. To achieve this, six genome-reduced strains and nine PrsA proteins were systematically selected based on their cultivation performance and the production of two reference amylases. Following strain selection and deletion of major extracellular proteases, several hundred individual strains were created and screened using a stepwise and modular automation approach combined with amplicon sequencing. In addition to providing the key learnings from the workflow, it was revealed that no single PrsA molecule consistently improved amylase production, but genetic constructs combining different elements showed up to a 10-fold variation in yield. Among the screened constructs, the signal peptides YdjM and YvcE demonstrated the best performance.